STUDI KUALITAS AIR BEBERAPA MATA AIR DI SEKITAR BEDUGUL, BALI (THE STUDY OF WATER QUALITY OF SPRINGS SURROUNDING BEDUGUL, BALI) - Arthana, I Wayan (Bumi Lestari Journal of Environment; Vol 7 No 1, 2012)
Spring is source of water that emerges automatically to the surface from the ground. Water samples were taken from springs at Gesing village, close to Buyan lake and at Teratai Bang Temple (PRTB), a temple in the central of Bedugul Botanical Garden. There were twenty three parameters of water quality measured and two microbiological parameters observed. Six of the twenty five parameters observed were over than standard namely BOD5, COD, Sulfide, Iron, Lead and Cadmium. The content of BOD5 at three springs (2.03 – 8.10 mg/l) the highest at PRTB and the lowest at Gesing and all are over standard of 2 mg/l. Cadmium that over standard of 0.01 mg/l is in Buyan spring (0.013 mg/l) and at PRTB (0.012 mg/l). The highest iron is in PRTB spring (0.463 mg/l) that has been over standard of 0.3 mg/l and much higher than that in Bali springs of Sanggalangit, Pemuteran and Banyuwedang (0.1567 – 0.1817 mg/l) also over iron content in Bali lakes that below 0.150 mg/l. Conductivity content in the springs (126-275 ?S/cm), is consistent to the total suspended solid (TDS) of 150-290 mg/l in which at the high TDS, the conductivity is high as well and vice versa. At Buyan spring, pH value is the lowest and a bit acid (6.07) that closes related to the highest content of sulfite (15.55 mg/l). Nitrate at the springs (3.388 – 6.735 mg/l) are high and much higher than that in Bali springs of Sanggalangit, Pemuteran and Banyuwedang (0.422 - 0.503 mg/l) also over than nitrate content in Beratan, Buyan and Tamblingan lakes that below 2.5 mg/l.
Keywords: spring, water quality, metals